Study on the structure of phenylacetate complexes of Zn(II) and Ni(II) - Nguyet, Trieu Thi; Hien, Dinh Thi (Vietnam Journal of Chemistry, 2012)
Phenylacetates of M(PAA)2 (M=Zn; Ni; PAA-: phenylacetate) were synthesized and characterized by nuclear magnetic resonance spectroscopy and electronic absorption spectroscopy. The results obtained from 1H-NMR, 13C-NMR and UV-vis showed that in the complexes Zn(II) and Ni(II) adopt square-planar and tetrahedral geometries, respectively